Alternatives to traditional pharmacy internships: a scoping review protocol. - Yousif Mohammed Alhassan Nasr, Sabreen; Keshavarzi, Fazlollah; Sookaneknun Olson, Phayom; Sawangjit, Ratree; Thabit, Abrar K; Jose, Jimmy; Bhatarasakoon, Patraporn (JBI Evidence Synthesis, 2025)
Objective: This scoping review aims to map the literature on alternative methods for completing pharmacy internship hours when onsite training is not feasible. Introduction: Traditional pharmacy internships have long played a key role in bridging academic learning with practical experience. However, global disruptions and an oversupply of pharmacy graduates have challenged this model. In response, many institutions have adopted alternative, technology-based training methods that minimize the need for face-to-face interaction. Despite their growing use, the diversity, effectiveness, and assessment of these alternative approaches remain underexplored. Eligibility criteria: All studies that discuss strategies for adapting pharmacy internship programs will be included. Reviews, mixed methods studies, qualitative studies, quantitative studies, and gray literature will be considered. All alternative methods for completing pharmacy internship hours, such as remote supervision, project-based learning, problem-based learning, simulation-based training, telepharmacy, and other approaches, will be considered. Methods: This review will follow the JBI methodology for scoping reviews. We will search literature from any cultural or geographical context that meets the eligibility criteria in Scopus, PubMed, Embase (Ovid), ERIC, Web of Science, as well as gray literature (ProQuest, informit.org, and the National Technical Reports Library) without any date restrictions. Evidence will be mapped using a predetermined data extraction form based on the review's objectives and presented in tabular format accompanied by a narrative summary. Review registration: Figshare https://doi.org/10.6084/m9.figshare.27022831.v2